KONSELING PADA IBU HAMIL DENGAN OBESITAS - Nanda; Rohani; Nurbaity; Untari Anggeni (LPPM STIKes Mitra Adiguna, 2024)
Counseling in pregnant women with obesity is counseling about an individual who is experiencing problems (client) is helped to feel and behave in a more pleasant atmosphere through interaction with someone who is problematic who provides information and reactions that stimulate clients to develop behaviors that allow clients to play a more effective role for themselves and their environment. Literature. The purpose of this literature study is to find out the current literature related to counseling in pregnant women with obesity.Method: This literature review was conducted by searching for studies on databases such as Pubmed and Google Scholar studies published in 2019-2023 in Indonesian and English. The results of the study search obtained as many as 10 journals related to counseling in pregnant women with obesity that met the inclusion and exclusion criteria of the study. Of the 10 journals observed, there are 5 journals that analyze obesity with complications in pregnancy, 2 journals that analyze physical activity in pregnant women, 3 journals that analyze nutrition in pregnant women. Based on this literature review, it can be concluded that the content of counseling in pregnant women with obesity is related to complications during pregnancy such as preeclampsia, gestational diabetes, hypertension, premature birth and it is important for a pregnant woman to pay attention to activity and nutrition during her pregnancy.